The Effectiveness of Management in Reducing The Abuse of Narcotic Drugs and Psychotropic Substances - Al-Hassan, Rasha Abdullah Abd (Universitas Muhammadiyah Sidoarjo, 2023)
This scientific article investigates the multifaceted nature of narcotic drugs and psychotropic substances, examining their causes of proliferation and far-reaching effects on society encompassing the social, economic, and political spheres. The study underscores the gravity of drug-related issues, characterizing them as a significant social menace that impedes intellectual and artistic progress while fueling organized crime. It delves into the influence of drugs in inducing criminal activities due to their profound impact on individuals' nervous and sensory systems, highlighting Iraq's historical concern with this issue. The research identifies various economic, social, and psychological factors contributing to drug proliferation and abuse within society. Furthermore, it elucidates the devastating consequences of drug abuse on individuals, emphasizing the erosion of personal responsibility and productivity, often resulting in chronic health conditions. The study underscores the critical role of shared responsibility among society members and regulatory authorities in combatting drug-related challenges, emphasizing that mere legal texts are insufficient without effective enforcement. These findings call for a comprehensive approach to address the global issue of drug abuse and its detrimental implications on society, urging collaborative efforts and proactive measures for prevention and control. Highlights: Drug abuse fuels organized crime and hinders societal progress, posing a grave threat. Various economic, social, and psychological factors contribute to drug proliferation. Collaborative efforts and effective enforcement are crucial to combat drug-related challenges and protect society. Keywords: Narcotic Drugs, Psychotropic Substances, Drug Proliferation, Organized Crime, Societal Impact